Phenotypic correlations between some external and internal egg quality traits in the Japanese quail (Coturnix coturnix japonica) - Kul, Selim; Seker, Ibrahim (Asian Network for Scientific Information, 2004)
In this study, it has been aimed to determine the internal and external quality traits of the quail eggs as well as the phenotypic correlation between these traits. Totally 202 Japanese quail eggs collected in three sequential days were used for this study. Eggs were obtained from 90 female quails, all at 20 weeks of age. The birds were housed as 1 male/3 female per cage of 40x30x30 cm at Quail Research unit of the Department of Zootechnia, Faculty of Veterinary Medicine, Firat University. The values related to egg weight, shape index, shell weight, unit surface shell weight, shell ratio and average shell thickness are found respectively as 11.28 g, 74.90%, 0.84 g, 45.98 mg/cm2, 7.47% and 0.231 mm; and the albumen index, albumen height, albumen weight, albumen ratio, yolk diameter, yolk height, yolk weight, yolk index, yolk ratio and the average values related to the haugh unit are found respectively as 9.37%, 3.80 mm, 6.75 g, 59.83%, 2.57 cm, 0.939 mm, 3.69 g, 36.70%, 32.71% and 85.73%. According to the results obtained in this research, almost all internal quality traits of the egg were changed at the significant levels depending on the change occurred in the egg weight with respect to the external quality traits of the egg. However, the yolk and shell rates changed opposite to the albumen ratio and the albumen index. As a result, it has been considered that it was possible to use the egg weight in determining the eggshell weight, shell thickness and the shell ratio instead of using these traits that are the determinants of the eggshell quality of the quail eggs. © Asian Network for Scientific Information, 2004.
Keywords: Egg; Phenotypic correlation; Quail; Quality traits